Dryinidae of the Eastern Palaearctic region (Hymenoptera: Chrysidoidea) - Olmi, Massimo; Xu, Zaifu (Zootaxa, 2015)
An updated revision of Eastern Palaearctic Dryinidae is presented. Six subfamilies, 17 genera and 160 species are treated. Descriptions, geographic distribution, known hosts, natural enemies and type material of each species are presented, together with illustrations of the main morphological characters and keys to the subfamilies, genera and species. Complete lists of references concerning the Eastern Palaearctic Dryinidae and their hosts are given. The lectotype is designated for Anteon flaviscapus Jansson, 1950. A new combination is proposed for Mirodryinus olmii (Móczár, 1983), comb. nov. (from Radiimancus Móczár). The following new records are reported: Aphelopus prolatus Mita & Olmi, 2014 and Gonatopus formicicolus Richards, 1939 from Sweden; Aphelopus querceus Olmi, 1984, Aphelopus serratus Richards, 1939 and Anteon reticulatum Kieffer, 1905 from Bulgaria; Gonatopus nigricans (R. Perkins, 1905) from Solomon Islands; Haplogonatopus oratorius (Westwood, 1833) from Germany and Sweden.